Violence in Latin America - Garmendia Lorena, Fausto (2011)
General review of violence in Latin America is done. Classification of violence is that of the World Health Organization’s. Violence in Latin America indices are presented, especially political violence, violence to children and adolescents, violence to women, adults and older adults, where high rates are noticed, with particular analysis in each country. Regional efforts to reduce violence rates are described. Comments on results of Peruvian Truth and Reconciliation Commission final report are done, especially on the Reparation Integral Plan to relieve violence consequences on victims. Health and Education Reparations are emphasized. In regards to the latter, creation of the Permanent Training Program for Violence Victims Integral Care, Faculty of Medicine, Universidad Nacional Mayor de San Marcos is presented, program that favors formation of undergraduate and postgraduate human resources to obtain complete recovery of violence victims as well as to promote health, contribute to construction of healthy communities, and achieve a culture of peace.